METHODICAL APPROACHES TO THE DEVELOPMENT OF THE ECONOMIC SECURITY INDICATORS OF THE ORGANIZATION - T. Krotenko (Publishing House of the State University of Management, 2018)
In the terms of the economic crisis, it is important issue for many Russian and for-eign enterprises - to maintain the stability of functioning. The article discusses the relevant methodical aspect of assessing the economic security level of the organization. The require-ments for safety indicators, their types, the procedure for determining the threshold values are considered in detail. The comparative characteristic of quantitative and qualitative indicators has presented, the approximate structure of the economic security indicators of the enterprise has considered. The formula for calculating the integral safety indicator and its graphical in-terpretation have given.